The method of circumstantial evidence applicable to the assessment of evidence and the direct evidence in the judgment of collusion, embezzlement and corruption of government officials (bribery) - Caballero Laura, Raúl (2020)
At the end of the hearing, in the judgment of collusion, embezzlement and corruption of government officials (bribery), it is not possible to file direct evidence. The «circumstantial evidence» should use the principles of formal logic: a) principle of identity, principle of contradiction, principle of excluded middle and sufficient reason; b) the standards stemming from experience (normative criteria or non-legal rules); c) scientifically accepted knowledge. The use of «deductive inference» as a method to interpret evidences is adequate. This «method of evaluating evidence» must be applied to the assessment of «direct evidence», as it is more effective to bring us closer to the truth.